Quality indices and their impact on the cost of equity of industrial companies in Brazil - Securato, Tom Pessoa (2022)
The following study provides a verification on whether assets with high quality indicators, such as gross margin, are traded at a premium over the others. As quality metrics, financial indicators commonly adopted by the market were used, such as gross margin, Ebit margin, Ebitda margin, ROE, ROA, EV/net revenue and EV/Ebitda. The research was characterized as quantitative, using accounting and market data from companies in the industrial sector, from January 1995 to June 2018, to verify the magnitude of quality premiums and their power to explain returns on assets. Initially, an analysis of the seven chosen quality metrics was conducted, taking into account the correlation and the average number of companies per year. Then, the two-stage methodology of Fama and MacBeth (1973) was adopted. For the first stage, the premium for quality indicators was calculated following the model developed by Fama and French (1992). The calculated quality premiums proved to be robust and statistically significant at 1% over the period analyzed. Then, to verify whether the calculated risk factors would be valid for estimating the cost of equity, the Fama and MacBeth (1973) methodology was used. The work verified that the quality factor composed by the ROE financial indicator is statistically significant in estimating the cost of equity when used in conjunction with the market beta factor. It was also found that the proposed 2-factor model presented an explanatory power (Adjusted R2) higher than the CAPM – 27% and 43%, respectively.